Human Capital in the Digital Economy: The Impact of Technology on the Labor Market in Agriculture and Logistics - Ptashchenko, Olena; Fedorovych, Iryna; Gavkalova, Nataliia; Kaplun, Yevhen (Indian Journal of Information Sources and Services, 2025)
The digital economy affects the success of the agricultural and logistics industry, however, the adoption of computer technology differs in these sectors, although they are interconnected. Another aspect is the impact of information technology on personal potential and the influence of employees’ qualifications on the success of innovation. The aim of our study was to determine the mutual influence of digitalization and human capital by survey analysis of workers of agricultural and logistics companies. The methods of analysis, synthesis, survey, statistical, graphical, and abstract and logical comparison were used in the research. An online survey was conducted of 1460 employees of the agricultural sector and logistics companies, who were divided into groups depending on their professional qualifications. The survey results were compared using the ttest. A higher level of awareness of information technologies and their practical use was identified among employees of logistics companies. Moreover, medium-level managers and company executives had a high level of knowledge and skills in working with digital technologies, while drivers, loaders, and lower-level workers had a lower than average level of skills. Among agricultural workers, there was a low level of awareness of information technology, and among the types of innovations, respondents mostly mentioned simple sensors for irrigation, soil temperature and moisture control. In contrast, the level of information technology skills among medium-level managers was above average and the highest among all agricultural workers. However, the information technologies of this group were used for logistics, financial, analytical operations, marketing, and communications. Managers of agricultural enterprises rated their digitalization skills below average, which was the main reason for the low implementation of innovations in agricultural processes in the agricultural sector.